Living with Metastatic Cancer: A Roadmap for Future Research - Tometich, Danielle B. (Cancers (Basel), 2020)
SIMPLE SUMMARY: Although people with metastatic cancer are living longer with their disease, they are faced with challenges that can interfere with their quality of life. These challenges include worsening disease, survival time, symptoms, distress, and financial problems. The aim of this review paper is to describe a framework to guide future efforts to address these challenges. The framework includes the risk factors (predisposing factors), triggers (precipitating factors), and responses (perpetuating factors) that contribute to the onset and maintenance of problems in living with metastatic cancer. We conclude by suggesting areas for future work to prevent problems, manage triggers, and reduce unhelpful responses. ABSTRACT: Living with metastatic cancer, or metavivorship, differs from cancer survivorship and has changed as novel treatments have increased survival time. The purpose of this narrative review is to describe factors that impact challenges in metavivorship within a conceptual framework to guide future research. This review focuses on the specific metavivorship outcomes of progressive disease, survival time, symptoms, distress, financial toxicity, and quality of life. We describe the predisposing, precipitating, and perpetuating (3P) model of metavivorship. Understanding the biological, psychological, and social 3P factors that contribute to the development and maintenance of challenges in metavivorship provides a roadmap for future research. Implications of this model include prevention by targeting predisposing factors, management of precipitating factors after onset of metastatic disease, and treatment of perpetuating factors to reduce symptoms and improve quality of life during the chronic phase of metavivorship. This can be accomplished through biopsychosocial screening efforts, monitoring of patient-reported outcomes, education and communication interventions, interdisciplinary symptom management, advance care planning, and behavioral interventions to cultivate psychological resilience.